Flocking and Rendezvous in Distributed Robotics - Francis, Bruce A.; Maggiore, Manfredi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This brief describes the coordinated control of groups of robots using only sensory input - and no direct external commands. Furthermore, each robot employs the same local strategy, i.e., there are no leaders, and the text also deals with decentralized control, allowing for cases in which no single robot can sense all the others. One can get intuition for the problem from the natural world, for example, flocking birds. How do they achieve and maintain their flying formation? Recognizing their importance as the most basic coordination tasks for mobile robot networks, the brief details flocking and rendezvous. They are shown to be physical illustrations of emergent behaviors with global consensus arising from local interactions. The authors extend the consideration of these fundamental ideas to describe their operation in flying robots and prompt readers to pursue further research in the field.  Flocking and Rendezvous in Distributed Robotics will provide graduate students a firm grounding in the subject, while also offering an authoritative reference work for more experienced workers seeking a brief but thorough treatment of an area that has rapidly gained in interest.
Introduction -- Models of Mobile Robots in the Plane -- Admissible Controls and the Robot Flocking Problem -- The Robot Rendezvous Problem: Limited Camera Range -- A Convoy Problem -- A Look into the Future: Flying Robots.
Keywords: Control engineering; Robotics; Automation; System theory; Control theory; Control, Robotics, Automation; Control and Systems Theory; Systems Theory, Control